Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Harga Terhadap Kepuasan Konsumen - Nuke Dyah Pangesti; Henry Casandra Gultom; Mochamad Fadjar Dharmaputra (LPPM Politeknik Pratama, 2026)
This study aims to empirically test the effect of product quality, service quality, and price on customer satisfaction at the Fatmawati branch of Optik B Riski Semarang. The study population was all customers who made purchases, with a sample of 120 respondents determined using a purposive sampling technique. Data were collected through a questionnaire and analyzed using IBM SPSS 27.0, including validity and reliability tests, classical assumption tests, multiple regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that product quality, service quality, and price have a positive and significant effect on customer satisfaction, both partially and simultaneously. The coefficient of determination indicates that the independent variables are able to explain customer satisfaction, while the remaining 46.5% is influenced by other variables outside this study.